Perlindungan Hukum Terhadap Masyarakat Pengguna Sistem Pembayaran Bitcoin Dan Investasi Bitcoin Di Indonesia Ditinjau Dari Hukum Perlindungan Konsumen - I Gede Hendrawan Saputra; I Dewa Putu Surya Wardana (Jurnal Pacta Sunt Servanda, 2021)
The current technological development is so fast, including in the world of economy. Technological developments in this economic aspect can be seen from the types of payment systems that are so developed. In this era of globalization, Bitcoin appears which can be used as a means of payment. Bitcoin is a new currency or electronic money created in 2009 by a person who uses the alias Satoshi Nakamoto. Bitcoin is mainly used in internet transactions without using intermediaries or not using bank services. In Indonesia, there is no regulation on Bitcoin itself. The absence of laws governing Bitcoin in Indonesia causes unclear legal consequences related to transactions using Bitcoin. The use of Bitcoin is commonly applied in Indonesia, but regulations regarding the currency used in Indonesia as a legal means of payment have been regulated in Law Number 7 of 2011 concerning Currency, which is only the rupiah currency that can be used, which raises questions about legality. bitcoin and the legal consequences of Bitcoin transactions as a means of payment in Indonesia. This will cause various legal problems, one of which is related to the aspect of legal protection for consumers who use bitcoin payments in the event of a loss when making payments through the bitcoin system. With the absence of specific regulations governing bitcoin payments, it can be said that this system is not certain to be safe to use because there is no legal certainty that regulates it